2002
DOI: 10.2188/jea.12.55
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Profiles and Health Status in Japanese Female Patients with Systemic Lupus Erythematosus: The Miyagi Lupus Collaborative Study.

Abstract: and The Miyagi Lupus Study Group 6 Psychological factors have been suspected to be associated with the development of systemic lupus erythematosus (SLE) and patients health status. However, psychological profiles among Japanese patients with SLE have been poorly understood. We started a prospective study of female patients with SLE in 1995. Using the baseline data from 279 patients in this prospective study, we cross-sectionally analyzed the relations of clinical factors and social factors to psychological fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…When we compared the perceived health and healthy aging between subjects with various marital statuses, older people who were unmarried scored lower on HAI than others. This result is consistent with those of Palner and Mittelmark (2002), who reported that married people have a higher level of perceived mental health than unmarried people. Being married might confer health advantages that influence perceived health.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When we compared the perceived health and healthy aging between subjects with various marital statuses, older people who were unmarried scored lower on HAI than others. This result is consistent with those of Palner and Mittelmark (2002), who reported that married people have a higher level of perceived mental health than unmarried people. Being married might confer health advantages that influence perceived health.…”
Section: Discussionsupporting
confidence: 92%
“…Being married might confer health advantages that influence perceived health. These could be, e.g., emotional support, instrumental support, and social exchange with the partner (Goldman et al 1995; Palner and Mittelmark 2002). However, we also found that older people who were divorced or widowed reported higher HAI scores than those who were unmarried, possibly because they receive emotional support from their children (Zunzunegui et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design have been described elsewhere. 12 , 13 This study was approved by the ethical review board of Tohoku University Graduate School of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…12 In this cohort study, changes in disease activity and atherosclerotic vascular events were chosen as outcome indicators. The associations between several dietary factors and the clinical course of SLE have been analyzed, and a previous analysis of 4-year follow-up data demonstrated an inverse association between vitamin C intake and the risk of active disease.…”
Section: Introductionmentioning
confidence: 99%
“…It is a comprehensive concept that reflects emotions such as happiness and life-satisfaction as well as the cognitive evaluation towards one's life [14]. Recently, some researchers have used ''ikigai'' directly and reported its associations with various health conditions [11,12,[14][15][16][17][18][19] including total mortality [17]. It has not been evaluated for its relationship with breast cancer risk, but we hypothesized that it would have a protective effect on breast cancer development.…”
Section: Introductionmentioning
confidence: 99%